Perbandingan Komik Indonesia dan Komik Terjemahan - Kuswara (STKIP Sebelas April Sumedang, 2020)
This study compares translated comics and Indonesian comics that are widely read by junior high school students. The research applies descriptive-analytic-comparative method. The research analyzes the ethics of comic writing on aspects of story, image, and language. Many translated comics display ethics related to life (discipline, love for one's own culture, love for the environment), while in Indonesian comics this type of ethics is not found. The ethical violation in the story aspect in translated comics is in the form of coercion of the will to others, while in Indonesian comics such cases only appear few. Ethical violations regarding the behavior of characters that are often found in translated comics are unethical behavior towards parents, teachers, and friends/others, while in Indonesian comics this case is not found. The comic titles read by the respondents were all from Japan, there were no Indonesian comics. Humor comics are the most widely read type of comics. The events in translated comics are generally from everyday life, while Indonesian comics often feature